#TITLE_ALTERNATIVE# - MURNANDITYO (NIM : 13206183); Pembimbing : Dr.Ir. Pekik Argo Dahono, ARIEF
Analysis of output current ripple of three phase inverters is presented in this final project. Analysis begins with deriving an expression for the arbitrary injection signal for discontinuous modulation. It is followed by derivation of rms value of output current ripple of three phase inverters as a function of modulation index. Moreover derivation and plotting of the output current ripple of three phase inverters, index modulation, and phase shift relationship is given. The analysis shows that the value of rms output current ripple decrease on high modulation index. When compared to symmetrical discontinuous PWM, asymmetrical discontinuous PWM gives less value of rms output current ripple. In addition, phase shift 30o lag gives reduced output current ripple of three phase inverters. The result of simulation verify the analysis